Audit and control in system development / Rosli Abas - Abas, Rosli (Faculty of Accountancy, 1992)
The objective of this study is to obtain the minimum standard applicable in the development, or comDuterized system. Discussion will be extent on the needs for computerized system to be controls and the needs for computerized system.